The form you want is probably (x-a)²+(y-b)²=r² because this is a circumference.
let me just show you a first approach to this type of transformations before moving on to your problem.
if you have an expression like this:
you can ALWAYS transform that into something like (x+z)²
x²+px+q²=(x+z)² ; p,q and zeR
now we only need to solve the system to find p and q
Now lets apply the above method.
lets work each square separately:
ok! we just found that
is equivalent to:
Repeat the procedure for y.
lets replace again in the first expression...
Remember also that the radius of this circumference is r²=145/4 => r=(√145)/2
And here you have your 'standard form':